Perceptions of Self-Efficacy and Anxiety in Mathematics: A Study of Secondary School Students in Pakistan - Zafar, Muhammad Waseem; Ali, Hakim; Hussain, Bashir (Pakistan Journal of Humanities and Social Sciences, 2024)
The relationship between students' self-efficacy in mathematics and their anxiety is a critical area of research, as it has significant implications for educational outcomes and student well-being. This study aimed to investigate the correlation between mathematics self-efficacy and anxiety among secondary school students. A correlational research design was employed, with the target population consisting of all male and female students enrolled in public and private schools in the Khanewal district. A stratified random sampling technique was used to select a sample of 1,386 students. Data were collected using a questionnaire that included two scales: the Mathematics Self-Efficacy Scale and the Anxiety Scale. Out of the 1,386 distributed questionnaires, 1,072 were returned, resulting in a response rate of 77%. The data were analyzed using descriptive statistics and Pearson's correlation method. Descriptive analyses revealed that students generally perceived their mathematics self-efficacy positively, while they reported higher levels of mathematics anxiety. Pearson’s correlation analysis (two-tailed) indicated a weak negative relationship between mathematics self-efficacy and mathematics anxiety. These findings suggest that enhancing students' mathematics self-efficacy may lead to a reduction in their mathematics anxiety.